La influencia del TLC con Estados Unidos en la evolución del alcance del concepto de orden público. La renunciabilidad de la mal llamada cesantía comercial (2012)
The influence of the commitments acquired by Colombia under its Free Trade Agreement (FTA) with the United States is analyzed in light of a ruling handed down on October 19, 2011 by the Civil Chamber of the Supreme Court Justice concerning a change in the scope of the concept of public policy, which served as the main argument to determine the renounceability of the benefit established in the first paragraph of Article 1324 in the Commercial Code. To that end, the analysis in this article is based on the “law and howIwantittocomeout” thinking developed by Professor Duncan Kennedy in his book Freedom and Constraint in Adjudication.